Climate control on the evolution of Late Pleistocene alluvial‐fan and aeolian sand‐sheet systems in NW Germany. (24th April 2013) - Meinsen, Janine; Winsemann, Jutta; Roskosch, Julia; Brandes, Christian; Frechen, Manfred; Dultz, Stefan; Böttcher, Jürgen
<x xml:space="preserve">Abstract</x> The Late Pleistocene was characterized by rapid climate oscillations with alternation of warm and cold periods that lasted up to several thousand years. Although much work has been carried out on the palaeoclimate reconstruction, a direct correlation of ice‐core, marine and terrestrial records is still difficult. Here we present new data from late Middle Pleniglacial to Lateglacial alluvial‐fan and aeolian sand‐sheet deposits in northwestern Germany. Records of Late Pleniglacial alluvial fans in central Europe are very rare, and OSL dating is used to determine the timing of fan aggradation. In contrast to fluvial systems that commonly show a delay between climate change and incision/aggradation, the small alluvial‐fan systems of the Senne area responded rapidly to climatic changes and therefore act as important terrestrial climate archives for this time span. The onset of alluvial‐fan deposition correlates with the climate change from warm to cold at the end of MIS 3 (29.3±3.2 ka). Strong fan progradation started at 24.4±2.8 ka and may be related to a period of higher humidity. The vertical stacking pattern of sedimentary facies and channel styles indicate a subsequrent overall decrease in water and sediment supply, with less sustained discharges and more sporadic runoffs from the catchment area, corresponding to an increasing aridity in central Europe during the Late Pleniglacial. Major phases of channel incision and fan aggradation may have been controlled by millennial‐scale Dansgaard–Oeschger cycles. The incision of channel systems is attributed to unstable climate phases at cold–warm (dry–wet) or warm–cold (wet–dry) transitions. The alluvial‐fan deposits are bounded by an erosion surface and are overlain by aeolian sand‐sheets that were periodically affected by flash‐floods. This unconformity might be correlated with the Beuningen Gravel Bed, which is an important marker horizon in deposits of the Late Pleniglacial resulting from deflation under polar desert conditions. The deposition of aeolian sand‐sheet systems (19.6±2.1 to 13.1±1.5 ka) indicates a rapid increase in aridity at the end of the Late Pleniglacial. Intercalated flash‐floods deposits and palaeosols (Finow type) point to temporarily wet conditions during the Lateglacial. The formation of an ephemeral channel network probably marks the warm‐cold transition from the Allerød to the Younger Dryas.